Avian strains of emerging pathogen Escherichia fergusonii are phylogenetically diverse and harbor the greatest AMR dissemination potential among different sources: Comparative genomic evidence - Srinivas, Kandhan; Ghatak, Sandeep; Pyngrope, Daniel Aibor; Angappan, Madesh; Milton, Arockiasamy Arun Prince; Das, Samir; Lyngdoh, Vanita; Lamare, John Pynhun; Prasad, Mosuri Chendu Bharat; Sen, Arnab (Frontiers in Microbiology, 2023)
Introduction Escherichia fergusonii is regarded as an emerging pathogen with zoonotic potential. In the current study, we undertook source-wise comparative genomic analyses (resistome, virulome, mobilome and pangenome) to understand the antimicrobial resistance, virulence, mobile genetic elements and phylogenetic diversity of E. fergusonii. Methods Six E. fergusonii strains (5 multidrug resistant strains and 1 biofilm former) were isolated from poultry (duck faeces and retail chicken samples). Following confirmation by phenotypic and molecular methods, the isolates were further characterized and their genomes were sequenced. Comparative resisto-virulo-mobilome analyses and pangenomics were performed for E. fergusonii genomes, while including 125 other E. fergusonii genomes available from NCBI database. Results and discussion Avian and porcine strains of E. fergusonii were found to carry significantly higher number of antimicrobial resistance genes (p < 0.05) and mobile genetic elements (plasmids, transposons and integrons) (p < 0.05), while the pathogenic potential of bovine strains was significantly higher compared to other strains (p < 0.05). Pan-genome development trends indicated open pan-genome for all strains (0 < γ < 1). Genomic diversity of avian strains was found to be greater than that from other sources. Phylogenetic analysis revealed close clustering among isolates of similar isolation source and geographical location. Indian isolates of E. fergusonii clustered closely with those from Chinese and a singleton Australian isolate. Overall, being the first pangenomic study on E. fergusonii, our analysis provided important cues on genomic features of the emerging pathogen E. fergusonii while highlighting the potential role of avian strains in dissemination of AMR.